ECONOMIA DA MONTANHEIRA , MULTIFUNCIONALIDADE DOS SISTEMAS E SUSTENTABILIDADE DOS MONTADOS - COELHO, INOCÊNCIO SEITA (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
In this paper we demonstrate how important the economics of the Black Pig Alentejano race is in “montanheira” production system to the conservation of the cork oak and holm oak “montados”. We demonstrate also that the “montado” system is essential to assure the high quality and high prices of the goods provided by Black Pig extensive production system
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: Alentejana Race Pigs; economics potential; environmental goods; high quality products; natural resources

EFECTO DE FERTILIZANTES SOBRE LA PRODUCCIÓN DE BIOMASA Y PARÁMETROS DE CALIDAD EN PASTOS HERBÁCEOS DE DEHESA DESPUÉS DE TRES AÑOS CONTINUADOS DE APLICACIÓN - SANTAMARÍA, O.; Poblaciones, M. J.; Olea, L.; Rodrigo, S.; VIGUERA, F. J.; GARCÍA-WHITE, T. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
Dehesa is an agrosilvopastoral system widespread in southwestern Iberian Peninsula. Natural pastures, which are the main source, could be improved by using a proper fertilization, among other practices. With the aim of evaluating the effect of different fertilizers on biomass production and sev- eral nutritive value parameters (crude protein, fiber and lignin) of the pasture in comparison with the traditionally used superphosphate, a study was initiated in 2006/07. In the present communication, the third-year-results (2008/09) are presented. The study was carried out in a dehesa located in Extre- madura, in two areas: one with natural pastures and other with sown pastures. Eight surface-broadcast fertilization treatments were done in autumn. Two grazing periods were simulated by cutting the pas- ture in middle-spring and late-spring. Although no statistical differences were found among treat- ments, fertilizers tended to increase biomass production in comparison to the non-fertilized control; in some cases (treatment M1in the sown pasture) increments were close to 50%. Regarding the nutritive value, treatment T2 (the highest doses of Thomaskali fertilizer, 300 kg·ha-1) produced biomass with the significant highest protein content
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: crude protein; fiber; Lignin; natural pasture; sown pasture

ESTADO NUTRITIVO DE LA ENCINA EN LAS DEHESAS Y SU RELACIÓN CON LA PRODUCCIÓN DE BELLOTA Y CON EL ESTADO DE VIGOR DEL ÁRBOL - GARCÍA MORENO, A. M.; LEAL MURILLO, J. R.; CARBONERO MUÑOZM. D; Fernández Rebollo, P. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
The present work tries to characterize the nutritional status of the holm oak, and analyzes the relations between nutrient content of the leaf with acorn production and tree health in dehesa farms from Los Pedroches. In October 2007, 126 leaf samples were collected from trees in nine different dehesa farms. These leaf samples were analyzed by means of conventional chemical methods to get macronutrients contents (N, P, K, Ca, Mg) and micronutrients contents (B, Cu, Fe, Mn, Zn). In addi- tion, acorn production and tree health (measured by defoliation rate) were estimated in each tree. The results show that the nutritional state of holm oak in dehesas gets acceptable levels. There are correla- tions between health tree and some nutrients (P, Mg and Mn), moreover, there are correlations be- tween K content and acorn production, and K content and relative water content of the leaf.
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: defoliation; nutrient content; water content

Modelización de la producción de pastos herbáceos en una dehesa del centro peninsular - Benavides, R.; ROIG, S.; Ponce, R. Alonso; López-Carrasco, C. (PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes, 2010)
Modelling pasture production and dynamics is a key objective for agroforestry systems man- agement for economic and conservation purposes. However, this is a complex task due to the large number of influencing factors and the characteristic diversity and heterogeneity of this production. The objective of this work is to analyze and model the pasture production in a dehesa of Central Spain. The study site is located in the Dehesón del Encinar (Toledo) state, in a low density dehesa (17 trees/ha). A first geostatistical approximation is used with data from two contrasted sampling years: 2008 and 2009. Sampling data include zones under tree influence and pasture without any canopy cover. Geostatistical techniques and GIS result to be efficient tools for analyzing and predicting pas- ture production as well as for agroforestry systems management. Key
The following values have no corresponding Zotero field: periodical: PASTOS: FUENTE NATURAL DE ENERGÍA 4ª Reunión Ibérica de Pastos y Forrajes pub-location: Zamora
Keywords: agro- forestry systems; geostatistical; herbaceous pastures; Mediterranean pastures; tree-pasture interaction